Pengaruh Persepsi Harga, Kualitas Pelayanan, dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Ulang melalui Kepuasan Pelanggan Mixue Ice Cream & Tea Samarinda - Mardalena Ardiyani; Ana Noor Andriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine how much effect of consumer behavior, such as price perceptions, service quality, and trust that consumer of Mixue ice cream & tea Samarinda get on repurchase decisions with customer satisfaction as an intervening variable. This is quantitative research with 110 primary data from questionnaires and using the Structural Equation Modelling (SEM) data analysis technique. Where the results show that perceived price, service quality and customer trust have a positive and significant effect on customer satisfaction. Price perceptions and service quality have a positive but insignificant effect on repurchase decisions, but customer trust has a positive and significant effect on repurchase decisions. And price perceptions have a positive but insignificant effect on repurchase decisions mediated by customer satisfaction, but service quality and customer trust have a positive and significant effect on repurchase decisions mediated by customer satisfaction.